Th e effects of the restructuring of power sector companies in terms of maintaining the energy security in Poland after 1989 - Szymla, Wojciech (Journal of Public Governance, 2014)
The article describes the progress, directions, and effects of structural and ownership transformations in the power sector in Poland in the past two decades, with a particular emphasis on their impact on energy security. In order to explain the objectives of the energy market reform, the paper introduces the concept and defi nition of energy security. The author characterizes the situation of the power sector at the beginning of the Polish political transformation, and the objectives of the government policy related to the reform. He uses the characteristics to present his own conclusions of the study on the effects of the reform in the power sector with regard to the condition of the Polish energy security, mainly from the point of view of energy consumers. The text closes with an analytical presentation of the main determinants of the structural transformation processes in the power sector in Poland, completing it with a short summary.